2020
DOI: 10.3390/agronomy10020217
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Control of Apple Scab with Targeted Spray Applications

Abstract: For two consecutive growing seasons (2017 and 2018), three different fungicide spray programs, each with five sprays from unrelated chemical groups, were evaluated for their effectiveness against apple scab (causal agent: Venturia inaequalis) in an experimental trial in Greece. The targeted application programs consisted of five sprays with protective and systemic fungicides from unrelated chemical groups, in alternation. The applications were started at the pink bud stage (a copper-based fungicide had previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In the Jammu and Kashmir state, this disease was reported in 1970s and ever since, it has caused havoc in the apple industry with the extent of fruit loss of up to 60%, estimating an amount in hundreds of crores [4]. V. inequalis, being a heterothallic haploid ascomycete, reproduces both sexually and asexually [3][4][5][6]. The disease takes the severe form in regions in which recurrent rainfall through the spring seasons leads into ascospore emancipation and infection [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Jammu and Kashmir state, this disease was reported in 1970s and ever since, it has caused havoc in the apple industry with the extent of fruit loss of up to 60%, estimating an amount in hundreds of crores [4]. V. inequalis, being a heterothallic haploid ascomycete, reproduces both sexually and asexually [3][4][5][6]. The disease takes the severe form in regions in which recurrent rainfall through the spring seasons leads into ascospore emancipation and infection [5].…”
Section: Introductionmentioning
confidence: 99%
“…It shall be noted that some limited research studies have managed to contain the disease by spraying only five chemical-based fungicidal compounds at critical growth stages of the crop [4,5]. Systemic fungicide sprays limited to seven in number have previously been able to contain the disease but due to the emergence of fungicide resistance in pathogens, these practices have become obsolete [6]. A recent survey in southeastern Europe has revealed the development of resistance in V. inaequalis against the potent fungicides dodine, pyraclostrobin, boscalid, difenoconazole, and cypradonil [11].…”
Section: Introductionmentioning
confidence: 99%
“…The other chemicals (mancozeb, metiram+pyraclostrobin) used in the present study had previously been reported to have good efficacy against PLF (Kumar & Sharma, 2014). Earlier studies also demonstrated the efficacy of tebuconazole +trifloxystrobin against scab disease of apple (Chatzidimopoulos et al, 2020), of fluxapyroxad+pyraclostrobin against powdery mildew disease of mango (Ravikumar et al, 2018) and of fluopyram+tebuconazole against PLF disease of apple (Verma & Khosla, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…Up to 15 fungicide sprays are executed annually to control potato late blight in Northern and Western Europe [5] and more than 20 fungicide sprays are applied to control rose mildew in some parts of the world [6]. In apple, more than 12 fungicide applications usually take place each season to control scab caused by Venturia inaequalis [7], even though a recent result indicated that only five applications could achieve the similar control purpose [8]. High resource inputs may usually increase gross production of crops but many of them may not generate positive net returns due to the gain in production being over-weighted by excess inputs.…”
Section: Introductionmentioning
confidence: 99%